Development of local wisdom-based Monita (Story Monopoly) media in folklore learning - Wulandari, Ayu; Burhanudin, Burhanudin; Firmadani, Fifit (ARKA INSTITUTE, 2023)
The lack of innovation in Indonesian language learning media on folklore material results in folklore being less attractive to students. Based on this, it is necessary to develop an interactive learning media so that it can attract and increase students' interest and learning outcomes in folklore material. This study aims to describe, develop, and determine the feasibility of Monita media (story monopoly) based on local wisdom The type of research used is Research and Development (R&D). The results of this study are to produce Monita (monopoly story) media development products based on local wisdom in learning folklore class VII SMP Negeri 2 Magelang. The research stages of developing Monita media (story monopoly) are as follows. (1) research and data collection, (2) planning, (3) product draft development, and (4) limited and small-scale use tests. The results of the Monita media assessment (story monopoly) obtained a percentage from material experts of 94%, a percentage from media experts of 89%, and a percentage from respondents of 94%. This means that the monita media is in the category of very feasible to use in learning Indonesian language folklore material.